Green Economy and Its Influence on Foreign Direct Investment in Indonesia - Ni Luh Ketut Ayu Sudha Sucandrawati (Nomico, 2025)
This study aims to analyze the impact of green economy policies on Foreign Direct Investment (FDI) flows in Indonesia, focusing on sectors that support sustainability, such as renewable energy, green technology, sustainable agriculture, and waste management. The approach used was a data panel regression analysis, which examined the relationship between green economic policies (independent variables) and FDI flows (dependent variables), with controls for macroeconomic variables such as GDP and inflation. The data used are secondary, obtained from reliable sources such as the Investment Coordinating Board (BKPM) and Bank Indonesia, with a period of 2010-2023.The results of the regression analysis show that green economy policies, including renewable energy and sustainable agriculture policies, do not have a significant influence on FDI flows. The insignificant coefficient and p-value on most variables indicate that the policy has not been effective enough in attracting foreign investment. Nonetheless, sectors related to green policies show the potential to increase FDI with improved policies and regulations. The conclusion of this study is that Indonesia needs to strengthen green economy policies, increase incentives, and improve infrastructure and regulations to attract more FDI in the green sector.